THE ESSENCE OF USING STEAM EDUCATION TECHNOLOGY IN PRIMARY EDUCATION (International journal of artificial intelligence, 2025)
This article provides a brief overview of STEAM educational technology and detailed information on the importance of using this technology in primary education.